STUDY THE RELATIONSHIP BETWEEN GHRELIN LEVEL AND SOME BIOCHEMICAL MARKER IN ANBAR CITY - 1 Abdulrahman Khalid Mssdf Albukhalefah **2 Şevki Adem, 3 Muhammad Hammad Jasim Alajeely, 4 Hussein Ali Nayyef Nayyef, (Chelonian Research Foundation, 2024)
The results showed that the sex of the patients in the four groups did not reveal any statistically significant differences in the averages of sex (males and females) between the two groups (controlling healthy people). The data showed that there was a significant difference between the averages of the gum disease patients, and the average age of the patients in the four groups included ranged the study ranged from 24.75 years in patients with obesity without the gum disease group to 32.55 years in patients with obesity and the gum disease group, and the data showed that ghrelin parameters varied in their effect on obesity and gum disease, which appeared in their values for the four tested groups studied. People suffering from obesity and gum disease showed the highest significant value in the level of ghrelin, as it was recorded at 189.90 mol/ml compared to 119.30 mol/ml for the control group. The results revealed that all groups of patients had a significant increase in the concentration of T3 compared to the healthy control group, and the patients also Those suffering from obesity without gum disease had a significant increase in T3 levels, which recorded 97.60 ng/dL with a standard deviation of 19.56, compared to 92.40 ng/dL with a standard deviation of 20.17 for the control group. The group of patients suffering from obesity without gum disease showed a low T4 level value, recording 6.96 micrograms/dL, while the control group recorded 7.73 micrograms/dL. The data showed that there was a significant difference in the average TSH level between the studied groups, as the TSH level in patients suffering from obesity and gum disease increased significantly, recording mIU/L with a standard deviation of 1.11 compared to 1.74 mIU/L with a standard deviation of 1.21 for the control group. Keywords: Obesity, Ghrelin, TSH, gum disease.